Chronic renal failure in equine due to ascending pyelonephritis predisposed by cauda equina syndrome: Case report - Granella M.C.S.* (2018)
© 2018 Universidade Federal de Minas Gerais.This report describes the case of a mare, of the Campeiro breed, used as an embryo donor, which had recurrent cystitis and urinary incontinence crisis. Clinical signs evolved to progressive weight loss, anorexia, apathy, and isolation from the group. Physical examination showed tail hypotonia, perineal hypalgesia, rectal and bladder sagging compatible with signs related to cauda equina syndrome. Complementary laboratory and sonographic assessment, and necropsy confirmed the diagnosis of chronic renal failure (CRF), which was attributed to the ascending pyelonephritis. The examination of urine culture showed growth of bacteria of the genus Streptococcus sp. This is a rare case in the equine species where the lower motor neuron dysfunction led the development of infectious process in the urinary tract, progressing to renal chronic condition incompatible with life.